A MODEL OF HUMAN RESOURCES DEVELOPMENT TO IMPROVE THE PERFORMANCE OF EMPLOYEES - Syafwandi, Syafwandi; Abdila, Syafiadi Rizki (Jurnal Aplikasi Manajemen, 2023)
In recent years, the Indonesian government has established priority programs to improve the accessibility and quality of health services throughout the country, including in rural and remote areas. However, many regional hospitals, including in the Besuki Raya area, experience various challenges in improving the quality of health services, especially in terms of employee performance. This study aims to determine the relationship between work ability, organizational culture, organizational climate, and work ethic on employee performance through organizational commitment and work motivation as intervening variables at Besuki Raya Hospital, East Java. This relationship pattern is explained through a structural equation model with opportunities and work motivation as intervening and endogenous variables. The sampling technique in this study was proportional area sampling which included employees of Besuki Raya Hospital consisting of Jember, Banyuwangi, Bondowoso and Situbondo, with 250 respondents willing to fill out the questionnaire. The study results show that workability, organizational culture, organizational climate, and work ethic significantly positively affect employee performance, directly and indirectly, through organizational commitment and work motivation. Hospital management must focus on human resource development and determine appropriate strategies to improve employee performance, including training, recognition, rewards, and effective communication. The implication of this research is that hospitals and local governments can improve human resources to improve the quality of health services to the community.